2018
DOI: 10.21449/ijate.408957
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Dynamic Criteria Mapping Assessment on Students’ Conceptions and Writing Skills Development

Abstract: Learner center assessment procedure and application is very crucial for students writing skills improvement. Hence, this study aimed to explore the effects of dynamic criteria mapping assessment on students' conceptions and writing skills development with reference to Vygotsky, zone of proximity development. To examine the issues, time series, quasi experimental research design was employed. The major data gathering tools were pre and post-tests, questionnaire and focus group discussion. Multistage sampling te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…These indicated that students' engagement was disregarded in the conventional academic writing instruction. This seemed to be the reason that engineering students developed negative conceptions towards improving their writing skills (Birhan, 2018).…”
mentioning
confidence: 99%
“…These indicated that students' engagement was disregarded in the conventional academic writing instruction. This seemed to be the reason that engineering students developed negative conceptions towards improving their writing skills (Birhan, 2018).…”
mentioning
confidence: 99%